DISTRIBUSI INVERS GAMMA PADA INFERENSI BAYESIAN - Sugito, Sugito; Ispriyanti, Dwi (MEDIA STATISTIKA, 2010)
One of the methods which can be used in statistical inferences is Bayesian inference. It is combine sample distribution and prior distribution, that can be resulted posterior distribution. In this article, sample distribution use univariate normal distribution. If prior distribution for variance with known mean is gamma inverse distribution, then posterior distribution is formed gamma inverse distribution. If Prior distribution use non-informative prior, then have the posterior distribution, by the marginal distribution of mean and varian. Also posterior distribution formed by gamma inverse distribution. Keywords: Gamma Inverse Distribution, Posterior Distribution, Non-Informatif Prior